Emergency rescuers: duties and liabilities / Mohd Royzal Abdul Razak...[et al.] - Abdul Razak, Mohd Royzal; Mohamad Hamidi, Norhuda; Ab. Talib, Intan Nordiana; Megat Mohd Ghazali, Megat Aiman Taher (Faculty of Law, 2009)
This project paper is a study on the duty and liability of the rescuers in Malaysia. During disasters and emergencies, rescue teams have actively participated in the rescue operations to save the lives of the victims who are in peril. In Malaysia, there are two types of the rescue teams; namely government and its agencies and the nongovernment agencies. The liability of the government rescue bodies is covered by the Government Proceedings Act 1956, Public Authorities Protection Act 1948, and any other related provisions in Malaysia. However, there is no specific legislation and provision that covers the liability of the volunteer rescuers in Malaysia. This project paper has referred to the legislation of Canada to consider the duty and liability imposed on the rescuers. There has two type of legislation that covers the liability of the rescuers in Canada, namely The Quebec Charter of Human Right and the Good Samaritans Act. In United Kingdom, the rule of Common law applies the neighbourhood principle which derived from the case of Donoghue v Stevenson [1932] AC 562. However, there is no legal obligation imposed to the rescuers concerning their duty and liability during the rescue operation. The outcome of the project paper is the proposed recommendations of law concerning the duty and liability of volunteer rescuer in Malaysia.